Determinants of Educator Satisfaction in Public Bureaucracy: The Dual Influence of Service Quality and Organizational Performance in the Indonesian Education Office - Ulansari, Ita; Hazin, Mufarrihul; Widiyanah, Ima (IKIP Widya Darma Surabaya, 2025)
Objective: This study examines the partial and simultaneous effects of service quality and organizational performance on the satisfaction of educators and education personnel in regional education bureaucracies in Indonesia. This study addresses a critical gap in understanding internal customer satisfaction in public education institutions. Method: A quantitative survey design was used, with data collected from 380 educators and civil servant staff at the Bojonegoro Regency Education Office using a validated 5-point Likert-type questionnaire. Statistical analysis included descriptive statistics, classical assumption tests, and multiple linear regression using SPSS 31.0. Results: Both service quality (β = .809, R² = 65.5%) and organizational performance (β = .920, R² = 84.6%) significantly influenced educator satisfaction. Together, they explained 87.5% of the variance in satisfaction. Although all SERVQUAL dimensions were rated positively, empathy (R=4.45) and efficiency aspects showed room for improvement compared to physical facilities (R=4.63). Novelty: This study provides empirical evidence on the dominance of organizational performance over service quality in determining internal satisfaction within the education bureaucracy. It offers contextual insights into Indonesian public sector reform, particularly highlighting the need for empathetic service delivery alongside structural improvements.